The Relationship of Achievement Motivation and Learning Interest with Student Learning Outcomes on The Topic Human Digestive System - Luthfiana Gita Pramesti; Budi Utami; Baskoro Adi Prayitno (Universitas Sebelas Maret, 2021)
This study aims to determine the relationship between achievement motivation and interest in learning with class student learning outcomes on the topic of the human digestive system. This research uses quantitative correlation method. Sampling using proportional random sampling technique. Participants in this study amounted to 185 students. Data collection techniques used are questionnaires and tests. Questionnaire to measure achievement motivation, interest in learning and affective learning outcomes. The test is used to measure cognitive learning outcomes. The results of the test and questionnaire reliability test are indicated by Cronbach's Alpha r values of 0.954, 0.917, 0.946, and 0.757 and are said to be reliable. The data analysis used is correlation and regression analysis. The results of the study indicate that there is a positive and significant relationship between achievement motivation and student learning outcomes. There is a positive and significant relationship between interest and student learning outcomes. There is a correlation between achievement motivation and interest in learning together with student learning outcomes on the topic of human digestion.